Effect of Serum Vitamin D Content on the Clinical Course of Psoriasis - Ubaid Ullah Khan, Zhu Ya Lin, Ubaid Ullah, Sajid Ghafoor, Qazi Syed Irfan Ullah Shah, Muhammad Waqas, Saddam Hussain, Junaid Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the incidence of serum vitamin D insufficiency in patients with psoriasis and study the relationship between dietary intake of vitamin D and clinical characteristics. Materials and Methods: Totally eighty individuals were enrolled and were equally divided into two groups (40 patients in each group): Group A consisted of psoriasis patients, whereas Group B consisted of controls. By using the PASI scale, psoriasis plaques were identified and assessed. The predesign questionnaire was developed and was given to each participant to complete it. Age, gender, the length of the psoriasis, concurrent illnesses, and medications were among the collected data. A dermatologist examined all of the patients and gathered information about their demographics, health, and any other pertinent information. Blood samples were taken to measure the level of serum vitamin D using the immuno-enzyme method. All measurements were conducted during winter months to avoid the influence of sun exposure on synthesis of vitamin D3 and its derivative 25-hydroxycholecalciferol. SPSS (v 25.0) was used for analysis and the results were shown in the form of graph and table. Results: Statistically significant difference was found in 25(OH) D3 levels between psoriasis affected individuals and healthy individuals. Both groups have low level of 25-hydroxycholecalciferol. In our results there is negative correlation between 25(OH) D3 and PASI. There is also a negative correlation between 25(OH) D3 and duration of psoriasis. Practical implication: This study will help the clinical practitioner to advise the patients with psoriasis to use enough amounts of vitamin D3 that will help to normalize the vitamin D level in patients. It is believed that psoriasis can cause a progressive decrease in the level of vitamin D3 derivatives in the whole human body, including the skin. So vitamin D rich food must be eaten in high amount. Conclusion: It is found in this study that both the groups have low serum vitamin D3 level. Both the general public and persons with psoriasis should eat enough amounts of vitamin D3. Keywords: PASI, vitamin D3, Psoriasis, serum, antiproliferative,